Incidence of delirium in the Canadian emergency department and its consequences on hospital length of stay: a prospective observational multicentre cohort study. Issue 3 (8th March 2018) - Émond, Marcel; Boucher, Valérie; Carmichael, Pierre-Hugues; Voyer, Philippe; Pelletier, Mathieu; Gouin, Émilie; Daoust, Raoul; Berthelot, Simon; Lamontagne, Marie-Eve; Morin, Michèle; Lemire, Stéphane; Minh Vu, Thien Tuong; et al.
Abstract : Objective: We aim to determine the incidence of delirium and describe its impacts on hospital length of stay (LOS) among non-delirious community-dwelling older adults with an 8-hour exposure to the emergency department (ED) environment. Design: This is a prospective observational multicentre cohort study (March–July 2015). Patients were assessed two times per day during their entire ED stay and up to 24 hours on hospital ward. Setting: The study took place in four Canadian EDs. Participants: 338 included patients: (1) aged ≥65 years; (2) who had an ED stay ≥8 hours; (3) were admitted to hospital ward and (4) were independent/semi-independent. Main outcome(s) and measure(s): The primary outcomes of this study were incident delirium in the ED or within 24 hours of ward admission and ED and hospital LOS. Functional and cognitive status were assessed using validated Older Americans Resources and Services and the modified Telephone Interview for Cognitive Status tools. The Confusion Assessment Method was used to detect incident delirium. Univariate and multivariate analyses were conducted to evaluate outcomes. Results: Mean age was 76.8 (±8.1), 17.7% were aged >85 years old and 48.8% were men. The mean incidence of delirium was 12.1% (n=41). Median IQR ED LOS was 32.4 (24.5–47.9) hours and hospital LOS was 146.6 (75.2–267.8) hours. Adjusted mean hospital LOS was increased by 105.4 hours (4.4 days) (95% CI 25.1 to 162.0, P<0.001) for patients who developed an episode of delirium compared with non-delirious patient. Conclusions: An incident delirium was observed in one of eight independent/semi-independent older adults after an 8-hour ED exposure. An episode of delirium increases hospital LOS by 4 days and therefore has important implications for patients and could contribute to ED overcrowding through a deleterious feedback loop.